Protocatechualdehyde attenuates oxidative stress in diabetic cataract via GLO1-mediated inhibition of AGE/RAGE glycosylation - Cheng, Xiao; Zhao, Sixuan; Chen, Yucai; Wang, Jiawei; Han, Furong (Frontiers in Pharmacology, 2025)
BackgroundProtocatechualdehyde (PCA), a phenolic compound derived from Salvia miltiorrhiza, exhibits anti-proliferative and antioxidant properties. However, its molecular mechanisms in reducing oxidative stress in diabetic cataract (DC) remain unclear. This study systematically investigated the role of PCA in modulating glyoxalase-1 (GLO1)-dependent suppression of advanced glycation end product (AGE)-receptor for AGE (RAGE) axis activation and oxidative stress in DC models.MethodsA galactose-induced DC rat model and high glucose-stimulated human lens epithelial cells (HLECs) were employed. Lens opacity was assessed using slit-lamp microscopy. GLO1, AGE, and RAGE expressions were analyzed through immunohistochemistry (IHC), immunofluorescence (IF), ELISA, and Western blotting. Molecular docking was performed to validate PCA–GLO1 interactions.ResultsPCA administration (25 mg/kg) significantly alleviated lens opacity and epithelial cell disorganization in DC rats (p < 0.01). In vitro, PCA (10 μM) restored HLEC viability under hyperglycemic conditions (p < 0.05). Mechanistically, PCA upregulated GLO1 expression while suppressing AGE accumulation and RAGE activation in both models. Molecular docking revealed strong binding affinities between PCA and GLO1 (-CDOCKER energy: 26.41 kcal/mol).ConclusionPCA ameliorates DC progression by enhancing the GLO1-mediated detoxification of AGE precursors, thereby inhibiting AGE/RAGE-driven oxidative stress. These findings provide a foundation for PCA as a therapeutic candidate for DC.